DEVELOPMENT OF A BIOMIMETIC SENSOR MODIFIED WITH HEMIN AND GRAPHENE OXIDE FOR MONITORING OF CARBOFURAN IN FOOD - Wong, Ademar [UNESP]; Materon, Elsa Maria [UNESP]; Taboada Sotomayor, Maria Del Pilar [UNESP] (Elsevier B.V., 2014)
A biomimetic sensor based on a carbon paste electrode modified with hemin complex and graphene oxide was developed as an alternative technique for the sensitive and selective analysis of carbofuran pesticide. The electrochemical analysis of carbofuran was initially carried out with the biomimetic sensor using cyclic voltammetry within the potential range of -0.2 to 0.8V vs. Ag/AgCl (KClsat). The sensor showed in square wave voltammetry (SWV) a linear response between 5.0 x 10 (6) and 9.5 x 10 (5) mol L (1), a sensitivity of 1.1 x 105 (+1.4 x 103) pA L mol 1 and detection limit of 9.0 x 10 (9) mol L (1). The sensitive and selective detection of carbofuran was confirmed through the analysis of other pesticides using SWV. When the proposed sensor was applied in food samples, the results obtained in the recovery studies were found to be close to 100%. These results obtained were similar to those of the high performance liquid chromatography (HPLC) method. Furthermore, an electrochemical study was conducted aiming at verifying the importance of the use of hemin complex and graphene oxide in the construction of the sensor. The results obtained showed a clear improvement in selectivity, reproducibility and sensitivity of the proposed sensor. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Biomimetic sensor; P450 enzyme; carbofuran; hemin; carbon past; graphene oxide